The Benefits of Fine Art Integration into Mathematics in Primary School - Anja Brezovnik (Center for Educational Policy Studies Journal, 2015)
The main purpose of the article is to research the effects of the integration of fine art content into mathematics on students at the primary school level. The theoretical part consists of the definition of arts integration into education, a discussion of the developmental process of creative mathematical thinking, an explanation of the position of art and mathematics in education today, and a summary of the benefits of arts integration and its positive effects on students. The empirical part reports on the findings of a pedagogical experiment involving two different ways of teaching fifth-grade students: the control group was taught mathematics in a traditional way, while the experimental group was taught with the integration of fine art content into the mathematics lessons. At the end of the teaching periods, four mathematics tests were administered in order to determine the difference in knowledge between the control group and the experimental group. The results of our study confirmed the hypotheses, as we found positive effects of fine art integration into mathematics, with the experimental group achieving higher marks in the mathematics tests than the control group. Our results are consistent with the findings of previous research and studies, which have demonstrated and confirmed that long-term participation in fine art activities offers advantages related to mathematical reasoning, such as intrinsic motivation, visual imagination and reflection on how to generate creative ideas.